Manajemen Supervisi Akademik dalam Meningkatkan Kinerja Guru: Studi Kasus pada SMK Tarbiyatunasiin Jombang Jawa Timur - Elis Lisyawati; Khairuniisa; Rika Opsari; Warka Warta; Che Ahmad (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
So far, school principals have been preoccupied with administrative matters, often neglecting supervision activities that play a role in maintaining the quality of education. Academic supervision management is not only able to improve teacher performance but will also have an impact on the quality of education that is able to produce superior human resources, and able to compete globally. The purpose of this study is to find out how the academic supervision management carried out by the head of SMK Tarbuyatunnasiin in improving teacher performance. This research uses qualitative methods with three main techniques in data collection, namely observation, in-depth interviews, and documentation. To ensure data validity, researchers applied triangulation techniques by validating data through programme documents and other written evidence. The combination of various data collection techniques and triangulation aims to produce valid and reliable data, related to the implementation of academic supervision in improving teacher performance at SMK Tarbiyatunnasiin. Jombang East Java. Academic supervision is in line with Gaol's (2018) opinion, especially the principal's efforts to improve teacher competence and performance, such as the ability to design lesson plans that are relevant to the SMK curriculum, skilled in determining and utilising innovative learning methods that are relevant to the vocational field, and good use of technology in the learning process. However, in the follow-up activities, the head of SMK Tarbiyatunasiin has not maximally included all education personnel to attend training either held by the school or outside the school due to constraints on competence, knowledge and adequate budget.